THE ESSENCE OF THE DEVELOPMENT OF NATIONAL CHARACTERISTICS IN STUDENTS THROUGH WORKS OF ART (Intent Research Scientific Journal, 2024)
In this article, the possession of national character qualities serves the perception of national identity. And the understanding of national self is about ensuring that the individual is not dependent on others, is not subject to others and his rights are not infringed, and the person who is not subject to others is free, independent and able to demonstrate his potential in all spheres of social life, the free and independent activities of citizens, which in turn lead to the creation of material and spiritual wealth that will ensure the development of society.